Dual descriptions of massive spin-3 particles in D=2+1 via Noether gauge embedment - Mendonca, E. L. [UNESP]; Dalmazi, D. [UNESP] (Amer Physical Soc, 2015)
We present here a relationship among massive self-dual models for spin-3 particles in D = 2 + 1 via the Noether gauge embedment (NGE) procedure. Starting with a first-order model (in derivatives) S-SD(1) we have obtained a sequence of four self-dual models S-SD(i) where i = 1; 2; 3; 4. We demonstrate that the NGE procedure generates the correct action for the auxiliary fields automatically. We obtain the whole action for the fourth-order self-dual model including all the needed auxiliary fields to get rid of the ghosts of the theory.